Pre-operative Embolization as Resection Strategy in Brain Tumor with No Neurological Deficit - Sendjaja, Andi N.; Rosbianto, Yogi; Sutiono, Agung B.; Zulkifli, Bilzardy F.; Sidabutar, Roland; Adam, Achmad; Arifin, Muhammad Z. (Journal of Medicine and Health, 2018)
Meningioma is an intracranial tumor that generally involves meninges. This tumor can be found along the dura layers at the skull base. Meningioma has vast vascularization from the arteries near dura attachment. Pre-operative embolization technique is an effective strategy to prevent intra-operative complications and better outcomes. The patient was a 24 year-old woman who has been complaining of headaches since 2 months ago. The CT Scan resulted in a 12 x 9 x 7 cm isodense mass in the left temporoparietal enhanced homogenously by contrast. Pre-operative embolization was performed on the tumor feeding artery as a strategy to prevent intra-operative blood loss. A left frontotemporosphenoidal craniotomy was performed 10 days after embolization to remove the tumor. A complete resection was successfully achieved with less intraoperative blood loss and without complication. The pathology examination resulted in meningotheliomatous meningioma. A follow-up picture showed no recurrent tumor after resection and the patient had no symptoms and neurological deficits until 6 months after the surgery. In conclusion, meningioma is a common intracranial tumor with a lot of blood supply. However, tumor resection can be safely and efficaciously performed with good pre-operative strategy. Keywords: brain tumor, embolization, meningioma, resection, skullbase